Stakeholder participation in IPBES: connecting local environmental work with global decision making. Issue 1 (1st January 2020) - Krug, Cornelia B.; Sterling, Eleanor; Cadman, Timothy; Geschke, Jonas; Drummond de Castro, Paula F.; Schliep, Rainer; Osemwegie, Isimemen; Muller-Karger, Frank E.; Maraseni, Tek
ABSTRACT: The Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services(IPBES) strengthens the science-policy interface by producing scientific assessments on biodiversity and ecosystem services to inform policy. IPBES fosters knowledge exchange across disciplines, between researchers and other knowledge holders, practitioners, societal actors and decision makers working at different geographic scales. A number of avenues for participation of stakeholders across the four functions if IPBES exist. Stakeholders come from diverse backgrounds, including Indigenous Peoples and local communities, businesses, and non-governmental organization. They represent multiple sources of information, data, knowledge, and perspectives on biodiversity. Stakeholder engagement in IPBES seeks to 1. communicate, disseminate, and implement the findings of IPBES products; 2. Develop guidelines for biodiversity conservation within member countries; and 3. create linkages between global policy and local actors – all key to the implementation of global agreements on biodiversity. This paper reflects on the role of stakeholders in the first work programme of IPBES (2014–2018). It provides an overview of IPBES processes and products relevant to stakeholders, examines the motivation of stakeholders to engage with IPBES, and explores reflections by the authors (all active participants on the platform) for improved stakeholder engagement and contributions to future work of the platform.